Challenging the Standard Model of Sexual Response: Evidence of a Variable Male Sexual Response Cycle. Issue 7 (1st September 2020) - Busby, Dean M.; Leonhardt, Nathan D.; Leavitt, Chelom E.; Hanna-Walker, Veronica
ABSTRACT: Historically the male sexual response cycle was seen as uniform and used as the standard for women. Recent research has suggested that men's sexual response cycle may vary more than previously thought. We asked 520 sexually active men between the ages of 18–73 to report on their sexual desire and arousal patterns during their last sexual experience. Using a latent class mixture model from retrospective sexual response data, we found five classes of desire and arousal patterns. These patterns were examined for associations with demographics, outcomes during the sexual experience, and outcomes for the global relationship. The experiences of arousal and desire appear to be indistinguishable for men in this sample. The Fluctuation sexual response class (19% of men) and the High sexual response class (40%) were significantly different from most of the other classes in duration of their sexual experiences and overall satisfaction with their sexual experiences. Still, most sexual response patterns were associated with healthy relational and sexual outcomes. Variability in the male sexual response cycle is important to acknowledge and normalize.